2022
DOI: 10.1111/apt.17170
|View full text |Cite
|
Sign up to set email alerts
|

Implications for sequencing of biologic therapy and choice of second anti‐TNF in patients with inflammatory bowel disease: results from the IMmunogenicity to Second Anti‐TNF therapy (IMSAT) therapeutic drug monitoring study

Abstract: Background: Anti-drug antibodies are associated with treatment failure to anti-TNF agents in patients with inflammatory bowel disease (IBD).Aim: To assess whether immunogenicity to a patient's first anti-TNF agent would be associated with immunogenicity to the second, irrespective of drug sequence Methods: We conducted a UK-wide, multicentre, retrospective cohort study to report rates of immunogenicity and treatment failure of second anti-TNF therapies in 1058 patients with IBD who underwent therapeutic drug m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…87 88 For each 10-fold increase in anti-TNF antibody concentration, the probability of developing antibodies to a subsequent anti-TNF increases has been estimated at 1.73. 89 Therefore, in patients with high anti-TNF drug antibody levels, switching within drug classes would be a better option than intensification. If a second anti-TNF is eventually considered, the experts recommend proactive TDM or close clinical monitoring along with adding an IMM.…”
Section: Open Accessmentioning
confidence: 99%
“…87 88 For each 10-fold increase in anti-TNF antibody concentration, the probability of developing antibodies to a subsequent anti-TNF increases has been estimated at 1.73. 89 Therefore, in patients with high anti-TNF drug antibody levels, switching within drug classes would be a better option than intensification. If a second anti-TNF is eventually considered, the experts recommend proactive TDM or close clinical monitoring along with adding an IMM.…”
Section: Open Accessmentioning
confidence: 99%
“…This latter approach is supported by recent evidence suggesting that patients with immunogenicity to previous anti-TNF therapy are more prone to developing antidrug antibodies against a subsequent anti-TNF agent. 40 , 41 …”
Section: New Insights For Proactive Tdm Of Biologicalsmentioning
confidence: 99%
“…Moreover, a systematic review reported that switching to a second anti-TNF agent led to successful induction of remission in 46% of patients with IBD who had failed the first anti-TNF agent[ 155 ]. Of note, the previous generation of anti-TNF antibodies increases the risk of the generation of a second anti-TNF antibody in IBD[ 156 ]. Therefore, when switching to another anti-TNF agent, a combination of immunosuppressive agents is appropriate[ 136 , 157 ].…”
Section: Optimal Management Of Anti-tnf Nonresponsementioning
confidence: 99%